Comparison of substrate reactivity of polyphenol oxidase and browning symptom of fresh cut 'Nam Dok Mai Si Thong' and 'Nam Dok Mai No. 4' mango in vitro and in vivo - Chimvaree, C.; Wongs-Aree, C.; Supapvanich, S.; Tepsorn, R.; Boonyaritthongchai, P. (My University, 2022)
'Nam Dok Mai Si Thong' and 'Nam Dok Mai No. 4' are popular cultivars for freshcut mango product in Thailand. Fresh-cut mango is considered as one of the most consumed products with the increasing market growth year by year. However, there are problems of fresh-cut mango due to surface browning and microbial contamination. This research was studied on the comparison of substrate reactivity of polyphenol oxidase and browning symptom of fresh-cut mango cultivars 'Nam Dok Mai Si Thong' and 'Nam Dok Mai No. 4'. Enzymatic browning of both 'Nam Dok Mai' mango revealed that polyphenol oxidase activity (PPO) in 'Nam Dok Mai Si Thong' was higher than 'Nam Dok Mai No. 4' mango. Five phenolic substrates of PPO including caffeic acid, catechol, chlorogenic acid, 4-methyl catechol and pyrogallol was individually dropped onto 'Nam Dok Mai Si Thong' and 'Nam Dok Mai No. 4' mango pulp surface for testing the specific substrates of 'Nam Dok Mai' mango's PPO (in vivo). 'Nam Dok Mai No. 4' mango cubes underwent darker browning symptom when treated with chlorogenic acid, 4-methyl catechol and caffeic acid, respectively, while 'Nam Dok Mai Si Thong' mango cubes showed a darker color when treated with 4-methyl catechol, catechol and pyrogallol. In vitro, the specificity of PPO activity of mango extract was determined using various substrates as caffeic acid, catechol, chlorogenic acid, 4-methylcatechol and pyrogallol. PPO extracted from 'Nam Dok Mai Si Thong' and 'Nam Dok Mai No.4' mango was more actively specific to catechol and 4-methylcatechol than other substrates which revealed the higher activity of PPO.
Keywords: enzymatic browning; Fresh cut mango